2013
DOI: 10.1177/0013161x12471832
|View full text |Cite
|
Sign up to set email alerts
|

When the “Dream” Turns Into a Nightmare

Abstract: Purpose: This article highlights the complexity of accountability issues associated with one charter school from the charter application process, operation, and functioning of the external mechanism and the internal mechanism to hold the charter school accountable, closure of the school, and consequences of the charter school's closure on its constituents. Research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…An intriguing study on the downfall of a charter school in Florida paints a picture of how conflict is an important element of adequate school board behaviour. This study showed that a lack of engagement in task‐related conflicts within the board appears to have ultimately ruined the school, for the school board “ did not question the principal on many issues regarding the school operations and finances ” (Karanxha, 2013, p. 600) and thus degenerated into a dysfunctional rubber‐stamping board. Previous research into the behaviour of supervisory school boards likewise suggests that task conflicts appear to have a positive effect on the task performance of school boards (Heemskerk, 2020; Heemskerk et al, 2015).…”
Section: Supervisory School Board Effectivenessmentioning
confidence: 95%
“…An intriguing study on the downfall of a charter school in Florida paints a picture of how conflict is an important element of adequate school board behaviour. This study showed that a lack of engagement in task‐related conflicts within the board appears to have ultimately ruined the school, for the school board “ did not question the principal on many issues regarding the school operations and finances ” (Karanxha, 2013, p. 600) and thus degenerated into a dysfunctional rubber‐stamping board. Previous research into the behaviour of supervisory school boards likewise suggests that task conflicts appear to have a positive effect on the task performance of school boards (Heemskerk, 2020; Heemskerk et al, 2015).…”
Section: Supervisory School Board Effectivenessmentioning
confidence: 95%
“…Because many state charter school statutes allow for charter schools to be closed for a variety of reasons, including the inability to be financially sustainable, districts that have failed to adequately provide financial resources to their charter schools have faced a variety of litigation, some based specifically on the availability of capital building resources (Karanxha, 2013; Lukasik, 2012). The state in which BCS resides allows charter schools to receive only state funding based on average daily membership and any federal funds to which their students are entitled, including Title I and IDEA (Individuals with Disabilities Education Act) funds; charter schools are not allocated any portion of locally collected taxes including local property tax or local sales tax revenue.…”
Section: Research and Backgroundmentioning
confidence: 99%